ASSESSMENT OF EFFECTIVENESS OF CRT INSTRUMENTS ON LEFT VENTRICULAR SYSTOLIC FUNCTION THROUGH DOPPLER ECHOCARDIOGRAPHIC PARAMETERS (Vietnam Journal of Community Medicine, 2022)
Objective: Evaluation of left ventricular function after CRT implantation.Subjects and research methods: The design of a comparative clinical trial before and after theintervention was carried out on 33 patients with heart failure who were implanted with CRT atBach Mai Hospital. Patients were evaluated for electrocardiogram, myocardial tension before CRTinsertion and after 1, 3 months and described clinical and laboratory features.Results: The study showed that the QRS interval improved statistically at the time of follow-upwhile the PQ interval improved later at 1 month and 3 months after implantation. Regarding leftventricular systolic function, left ventricular end-systolic volume decreased statistically, and leftventricular ejection fraction increased statistically at the time points after CRT implantation. Thetotal left ventricular longitudinal strain (GLS) also increased statistically significantly at the time offollow-up after intervention.Conclusion: Left ventricular function was significantly improved after CRT implantation in patientswith severe heart failure.
Keywords: Left ventricle, CRT pacemaker, heart failure.